Droplet collision with hydrophobic and superhydrophobic surfaces: Experimental studies and numerical modeling - Antonov, D.V.; Islamova, A.G.; Orlova, E.G.; Strizhak, P.A. (Surfaces and interfaces, 2024)
The characteristics of the collision of water droplets with textured hydrophobic and superhydrophobic surfaces obtained using two techniques were studied experimentally. The surface processing techniques are based on laser modification of the surface layer and changes in its chemical composition. Weber numbers in the experiments were varied in the range of 10–200. Regimes of water droplet-surface collision, the critical conditions for the transition between regimes, as well as integral characteristics of the formed liquid fragments were identified. The main characteristics of the process under study, such as the droplet spreading diameter, the height of its rebound from the surface, the number of secondary fragments during its break up were obtained experimentally. A model with a two-dimensional axisymmetric formulation was used to predict the characteristics of water droplet-textured surface collision based on the phase field method. The results of experimental studies and numerical modeling are in satisfactory agreement (differences of no more than 3–5 %). The conditions, when it is necessary to consider the values of static and dynamic contact angles during the modeling process, were determined. [Display omitted]